From Shipyard Workers to Young Precariat. Thirty Years of Research on Well-Ordered Economy at Warsaw School of Planning and Statistics (SGPiS)/Warsaw School of Economics (SGH) - Czarzasty, Jan (Warsaw Forum of Economic Sociology, 2018)
The article provides a retrospective overview of quantitative survey research on economic mentaility conducted in the Warsaw School of Planning and Statistics (SGPiS), renamed Warsaw School of Economics (SGH) in 1990. The time span of the research covered in the article runs from 1986 – when the initial surveys were completed – until 2016. The main focus is kept on so-called ‘well-ordered economy index’ (a set of variables designed to serve as a tool for reconstructing the dominant normative visions of economy) and its evolution over three decades. The most significant observation made is that despite profound changes in the structure of Polish economy and society which took place since the final years of the authoritarian state socialism, the normative visions of economy as registered by the research in focus have remained relatively stable.